Farmer-Fulani pastoralist conflicts in Northern Ghana: are integrated landscape approaches the way forward? - Bayala, E.; Ros-Tonen, M.; Sunderland, T.C.H.; Djoudi, H.; Reed, J. (Informa UK Limited, 2023)
Over the past 20 years, recurrent and violent conflicts between farmers and Fulani pastoralists have persisted in Northern Ghana. These conflicts mainly revolve around access to and utilisation of natural resources such as land and water. Conflicts of interest have led to the social marginalisation of the Fulani community, leading to their exclusion from formal landscape governance processes. This paper explores the prospects for better management of these conflicts and the potential for including Fulani pastoralists in landscape governance through the implementation of integrated landscape approaches. Based on a semi-systematic literature review and key informant interviews, we propose a categorisation of conflicts and potential causes and solutions. The experience of Burkina Faso in managing farmer-herder conflicts is presented to inform lessons for Ghana. We argue that adopting more inclusive landscape approaches, with a particular emphaisis on key principles, could contribute to reconciling diverging interests between farming and herding communities and help mitigate conflicts. This requires that constraints such as the negative and pervasive perceptions towards the Fulani, the neglect of pastoral activity in broader development processes, and the lack of inclusion of Fulani pastoralists in multi-stakeholder platforms and decision-making need to be urgently addressed.